Training center in the midst of the COVID-19 pandemic: what is the Indonesian Papuan elite athletes' happiness like? - Wandik, Y.; Guntoro, T. S.; Putra, M. F. P. (American Journal of Humanities and Social Sciences Research, 2021)
This study aims to reveal the differences in the happiness of Papua elite athletes during trainingcenter based on gender and sports classification. There are four sports in this study, namely softball, tarungderajat, archery, and climbing. The sample is 42 Papua elite athletes (21 males, 21 females) whose average age is 21.48 ± 4.54. The athletes` satisfaction was measured using the Satisfaction with Life Scale (SWLS) consistingof five statements. The data collection was conducted online with the Google form. The result shows (1) thelevel of satisfaction of Papua elite athletes in the training center during the crisis is in the "slightly dissatisfied"category; (2) there is no significant difference in satisfaction between male and female athletes, and all athleteswere reported in the same "slightly dissatisfied" category; (3) there is a significant difference in the level ofsatisfaction based on sports classification, and softball had the highest score compared to other groups, andclimbing had the lowest score with "dissatisfied" category.